2022
DOI: 10.1111/hdi.13004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the injection of low‐molecular weight heparin in the arterial vs. venous blood line for preventing extracorporeal circuit clotting during hemodialysis

Abstract: Low-molecular weight heparins (LMWH) are widely used for preventing clotting during hemodialysis (HD). Although injection in the venous blood line is recommended to avoid initial loss of LMWH through the dialyzer, LMWH is still frequently administered in the arterial blood line at the start of dialysis. This study aimed to compare the safety and efficacy of the same enoxaparin dose administered through the venous blood line or arterial blood line. We also evaluated antifactor Xa (aXa) activity according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The reduced bleeding risk observed in our study may be attributed to the use of LMWH and new oral anticoagulants in our patients. When administered at the same dose, LMWH generally carries a lower risk of bleeding than regular heparin 20 . This can be attributed to its more targeted action on coagulation factor Xa rather than thrombin 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced bleeding risk observed in our study may be attributed to the use of LMWH and new oral anticoagulants in our patients. When administered at the same dose, LMWH generally carries a lower risk of bleeding than regular heparin 20 . This can be attributed to its more targeted action on coagulation factor Xa rather than thrombin 21 .…”
Section: Discussionmentioning
confidence: 99%
“…When administered at the same dose, LMWH generally carries a lower risk of bleeding than regular heparin. 20 This can be attributed to its more targeted action on coagulation factor Xa rather than thrombin. 21 Furthermore, the newer oral anticoagulants demonstrate a relatively lower risk of bleeding than traditional oral anticoagulants while effectively preventing thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HDF as compared to HD removes larger molecules to a greater extent due to use of convection as compared to diffusion, which may also explain the difference in nadroparin clearance between these types of hemodialysis [6,30,31]. Some studies reported a significantly lower anti-Xa level in HDF versus high-flux hemodialysis (HF-HD), indicating a higher nadroparin clearance in HDF versus HF-HD [32,33]. However, Sridharan et al reported no difference in required LMWH dose to achieve adequate anti-Xa levels between HDF and HF-HD, suggesting no effect of dialysis mode on nadroparin clearance [34].…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines recommend dosing nadroparin based on the patient's body weight [5,6]. However, it has been stated before that higher nadroparin doses are needed in patients treated with HDF and that the type of dialyzer affects the required nadroparin dose [3,5,29,[32][33][34]. This has also been confirmed by our modelling analyses and model simulations, which demonstrated that the majority of patients on HDF had a zero probability of achieving the efficacy reference value throughout the entire HDF session.…”
Section: Discussionmentioning
confidence: 99%